The Role of Moral Education in Preventing Bullying in Islamic Boarding Schools: A Case Study - Arifin, Zainal; Afrudin, Afrudin (Jurnal Pendidikan Edutama, 2025)
Bullying among students is a serious issue that can affect their moral and social development. Moral education in Islamic boarding schools is expected to serve as a moral fortress to prevent bullying behavior. This study aims to examine the role of moral education in preventing bullying at Pondok Pesantren Al Ikhlash Sedayulawas, Brondong, Lamongan. Using a case study method, data were collected through in-depth interviews, participatory observations, and document analysis. The results indicate that moral education integrated into the daily activities of the boarding school can reduce the potential for bullying by instilling values of politeness, concern, and social responsibility. However, challenges in the implementation of discipline and exemplary behavior still pose obstacles that need to be addressed. This research provides insights into the importance of strong moral education as a solution to prevent bullying in the boarding school environment.